Relationship between organizational climate and job performance of agricultural extension workers in Iraq - Lafta, Ahmed Hamdan (2018)
There has been an extensive exploration on the association of organizational climate with the job performance in a large organizational context, predominantly in western countries. There is a considerable lacuna in understanding how the relationship of organizational climate dimensions and job performance determinants in developing countries especially Iraq. Meanwhile, recently three annual reports issued by the Ministry of Agriculture in Iraq (2013, 2014, 2015) mentioned that workers of extension are weak in their job performance. Actual study explores the dynamic relationship between organizational climate and job performance of the agricultural extension workers in Iraq with the view of providing situated understanding of how the dimensions of organizational climate have an influence on the determinants of job performance. For the organizational climate dimensions, the dimensions measurement is being used as conceptual Campbell et al. Theory (1970)from the literature review. While, the job performance determinants measurement by Porter et al. Theory (1968) is obtained also from literature. Organizational climate was measured using a validated instrument which included 76 questions. In contrast, the job performance was measured by 20 questions. Respondents were selected through the random sampling method to gather the data. Questionnaire were administered to 180 agricultural extension workers in Iraq whereby 53.76% are from the general headquarters, 22.57% are from training centers and 23.67% are from the typical extension farm. The quantitative data were analyzed through SPSS. The results show the majority of respondents’ perception is at medium level for organizational climate dimensions, job performance determinants and job satisfaction. The linear relationship between organizational climate and job performance is at 1% significance level. The coefficient value of 0.426 means were calculated based on Guilford’s Rule of Thumb: the strength of linear relation is moderate in a positive direction. As the conclusion, agricultural extension workers’ role in development and changing is substantial and certainly their attitude toward organizational climate and motivations towards work will correlate with the quality and caliber of their job performance with respect to their tasks. The literature in the field has established that job performance can be correlated by organizational climate among other factors. Therefore, it is recommended that the importance of a good incentive system in the agricultural extension organization are highlighted because of its impact on the job performance of extension workers where this study showed that there is insignificant in this dimension.